Frod dalam pengurusan syarikat: peranan dan cabaran pengarah syarikat masa kini - Azimon Abdul Aziz, (Fakulti Undang - Undang, 2002)

(untitled)
In every business world, ethics should come in parallel with the administration of each business organization. Nevertheless, there are countless administrative hurdles for each company to encounter with especially in relation to unethical and improper conduct during the company’s business operation. Fraud is the usual term used to describe a dishonest trick or criminal deception. Fraud has now become a practice for those who not only can we consider as ignorant of law but also those who knows and understand the law nevertheless neglect it due to business profits. In relation to the practice of ‘corporate governance’, director of company has now play an eminent role to ensure the growth and success of their company. Success and failure of company rest so much on the shoulder of its director. This article tries to highlight the practice of fraud in a company by its director and try to discuss legal provisions relating to the duties of director provided under the Companies Act 1965, taking into consideration the emergence of the Code of Corporate Governance. This is due to the fact that while directors are already subject to extensive laws and regulations regulating their conduct, their awareness of the extent of responsibilities attaching to their office appears to be minimal